Widespread occurrence of toxigenic Alternarias in cereals and oilseeds - and M.F. RAHMAN, K.S. BILGRAMI, K.K. SINHA, A.A. ANSARI (Indian Phytopathology, 2002)
A total of 76 isolates belonging to 4 different species of Alternaria (A. alternata 57, A. tenuissima 6, A. triticina 9 and A. brassicae 4) were collected from wheat, sorghum, kheri, cheena and mustard seeds. 67 per cent of these isolates (most of them) produced on moist rice medium five most important Alternaria mycotoxins are TA, AOH, AME, ALT and ATX-1. Majority of the toxigenic isolates of A. alternata produce TA, AOH, AME and ALT. ATX-1 was produced by few isolates only. Most of the toxigenic A. tenuissima produced TA, AOH and AME. A. triticina produced AOH, TA and ALT whereas A. brassicae produced AOH, AME and ALT. This is the first report of A. triticina as well as A. brassicae being the producers of these toxic metabolites.